A transversalidade da temática ambiental nos cursos técnicos de nível médio integrados ao ensino médio do Instituto Federal de Sergipe - Campus Aracaju - Costa, Juliano Azuma da (2017)
Environmental Education (EE) is undoubtedly a key tool for building a more environmentally conscious society. And, the school is considered a privileged environment for its development. For this, it is necessary that educational institutions insert in their documents and pedagogical practices the environmental theme. Thus, the objective of this research was to analyze the presence of the environmental theme, as a cross - sectional theme, in the High - Level Technical Courses Integrated to High School of the Federal Institute of Sergipe - Campus Aracaju. In this sense, the Institutional Political Project of the IFS, the Educational Projects of the Courses and the educational plans of the teachers were analyzed. Next, questionnaires were applied to students and teachers to analyze the presence of the environmental theme in the pedagogical practices in the classroom. The present study was descriptive, with explanatory character, with a predominantly qualitative approach, making use of two types of data collection instruments: documentary analysis and questionnaires. A total of 262 students and 63 professors from the Technical Courses of Middle Level Integrated to High School in Food, Buildings and Chemistry participated in this study. The results revealed that EE is still incipient in IFS. There is a need to reformulate institutional pedagogical documents so that they follow common guidelines in relation to EE and portray transversality. It was verified that the teachers and students understand the importance of EE and that the school plays a fundamental role in the contribution of the EE of society. Although the environmental theme is related to the contents of the subjects, it was verified that few times the theme is approached. The main difficulty presented by the teachers to work on the environmental theme in the classroom was the lack of preparation to deal with transversality in their activities in the classroom. It was suggested that a formal and non-formal EE policy be implemented through the awareness-raising and training of all actors involved in the IFS.